Atom Transfer Radical Copolymerization of Styrene and Poly(ethylene oxide)-alkyl Methacrylate Macromonomer - A. Ibrahim, Khalid (Asian Journal of Chemistry, 2010)
The present paper focuses on the atom transfer radical copolymerization of styrene and an amphiphilic macromonomer poly(ethylene oxide)-alkyl methacrylate (PEOm) which contains a hydrophilic polyethylene oxide segment and a hydrophobic alkyl chain. These block-copolymers were prepared using CuBr/bipy (bipy:2,2'bipyridine) catalyst system in conjunction with ethyl 2-bromoisobutyrate, as initiator, using o-xylene as a solvent at 90 ºC. The number-average molecular weights of the resulting block copolymers increased in direct proportion to the monomer conversion and the molecular weight distributions (Mw/Mn) were as low as 1.45. Thus a novel type of block-polymacromonomers with controlled chain lengths for both the backbone and the side chain have been synthesized. The resulting copolymers were characterized by means of room temperature gel permeation chromatograph and 1H NMR spectroscopy, FT-IR spectroscopy and differintial scanning calorimeter.